Development of Guided Inquiry-Based Electronic Modules and Its Effects on Students' Chemical Literacy - Mizwan Amrul Khairi; Jaslin Ikhsan (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
One effort to present abstract concepts is the use of learning media. Electronic can provide opportunities for students to learn independently without relying on them. This study aims to determine the feasibility and practicality of guided inquiry-based electronic modules, the difference in students’ chemical literacy abilities in each class, and the effectiveness of learning using guided inquiry-based electronic modules on students’ chemical literacy. This research is a 4D development model consisting of Define, Design, Develop, and Disseminate. This study was conducted at Senior High School 1 Tembilahan Hulu, and the participants were 60 high school students and five chemical teachers, and two validators– data collection in questionnaires and tests. This study used a quasi-experimental method and a post-test-only control group design. The data analysis technique in this research is a descriptive statistical analysis technique of percentages. The results showed that the feasibility of the product assessed by validators showed that the guided inquiry-based electronic module was proper to use in this research. The practicality of the chemistry teacher assessment shows a very good category, the chemical literacy of students who use guided inquiry-based electronic modules in learning is better than students who do not use guided inquiry-based electronic modules in learning. The effectiveness test showed that learning using an electronic module based on guided inquiry scored 0.74 in the medium category.